Estonian School System Strategic Leadership «Effects» on School Performance - Hasso Kukemelk (LED Edizioni Universitarie, 2015)
All Estonian comprehensive and vocational schools and kindergartens, introduced quality management principles based on the «European Foundation for Quality Management» (EFQM) model of excellence starting from September 2006. This study was designed to identify how school improvements towards learning organisations are managed according to the principal's opinion. The questionnaire was developed on the basis of EFQM excellence model criteria incuding five enablers (leadership, policy and strategy, people management, resources and processes) and four results (people satisfaction, customer satisfaction, impact on society, and business results). A five-point «Likert scale» was used in compiling the questionnaire, which was administered as an electronic survey (e-formular). All principals of Estonian elementary and secondary schools were asked to respond (63% answered) between November 2009 and February 2010. A total number of 327 school principals responded to the questionnaire. The sample was representative for Estonia and the tool was valid for measurement (Cronbach Alpha > 0.89 in major blocks of the instrument: strategic management, educational processes in school, assessment of school outcomes). The collected data were correlated to national educational statistics (state examination results, further studies, school drop-out, etc.). Average evaluations of school leadership statements by principals were extremely positive. The study indicates that after a three-year implementation of a new managerial system, principals use new terminology but most schools are continuing to run the previous system. The main points of the study are provided with a statistical overview and some recommendations for school development are offered.